RELASI ANGGOTA DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) DENGAN KONSTITUEN DAPIL III KECAMATAN PARIAMAN TENGAH KOTA PARIAMAN PROVINSI SUMATERA BARAT - Athahirah, Astika Ummy; Pranata, Wahyu Hadi (Fakultas Politik Pemerintahan, 2020)
Unestablished good relationship between members of the local parliament and constituents in 3rd Constituency, Central Pariaman Subdistrict, Pariaman City had caused difficulty to establish a good collaboration. A good relationship was intended to capture the aspirations of the community in finding solutions to community problems. This research aimed to get a description of the relationships between local parliament members and their constituents, inhibiting factors in relations, and efforts to solve inhibiting factors. The author used a descriptive method with a technique of data collection are semistructured interviews, observation, and documentation. As the results, the shape of relationships between Local parliament members and constituents freely mandate, the inhibiting factor in the relationship because the policy program of local parliament members has tried to make constituents not yet felt by the whole community, the lack of constituent awareness for legislative roles and the multiparty system created some local parliament members. To solve the problems are by political education, increasing the sense of care of local parliament members to their constituents. As the suggestion by adding a service function (serving to their constituent) into legislative function by using social media. Keywords: Relationships, Local Legislative, Constituent